THE EFFECT OF USING CIRCLE GAMES IN TEACHING VOCABULARY MASTERY AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 BATANG ANGKOLA - hasibuan, altri (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The purposes of this research are to find out: 1) the Application of using circle games in teaching vocabulary mastery. 2) Students’ vocabulary mastery before and after using circle games. 3) Whether there is a significant effect of using circle games at the eleventh grade of SMA Negeri 1 Batang Angkola. Method of this research is experimental method. The population of this research is the all of eleventh grade of SMA Negeri 1 Batang Angkola that consists of 230 students. Purposive sampling is used to get sample of research, the sample consist of 22 students. The result of the application of using circle games is 3,6 categorized “Very Good’. Before using circle games is 64,77 categorized “Enough”. Meanwhile, after using circle games is 97 categorized “Very Good”. The result of t test by using pair sample t test is the value of Sig (2-tailed) was greater than significant level (0,00<0,05), it means that there is a significant effect of using circle games in teaching vocabulary mastery at the eleventh grade of SMA Negeri 1 Batang Angkola. Keywords: vocabulary mastery, using circle games. Abstak: Tujuan dari penelitian ini adalah untuk mencari tahu: 1) Penerapan menggunakan permainan lingkaran dalam mengajarkan kosa kata. 2) Penguasaan kosa kata siswa sebelum dan sesudah menggunakan permainan lingkaran. 3) Apakah memang ada efek signifikan dari penggunaan circle games pada kelas xi di SMA Negeri 1 Batang Angkola. Metode penelitian ini adalah Eksperimental method, populasi dari penelitian ini adalah kelas xi dari SMA Negeri 1 batang angkola yang terdiri dari 230 siswa. Purposive sampling digunakan untuk mendapatkan sample penelitian, sample penelitian terdiri dari 22 siswa. Hasil dari penggunaan circle games adalah 3,6 categori “sangat baik” . Sebelum menggunakan circle games adalah 64,77 kategori “cukup”, dan setelah menggunakan circle games adalah 97 kategori “sangat baik”. Hasilnya sering kali adalah dengan menggunakan pair sample ttest nilai dari (sig 2) lebih besar daripada tinggkatannya, itu berarti bahwa ada pengaruh signifikan dari menggunakan permainan lingkaran dalam mengajarkan kosa kata pada kelas xi di Sma negeri 1 Batang Angkola. Kata Kunci: Penguasaan kosakata, menggunakan permainan lingkaran.